The Attractiveness of Regional Towns: Inferring Quality of Life From Higher Education Facilities - Drummond, Aaron; Palmer, Matthew A.; Halsey, R. John (Australian and International Journal of Rural Education, 2013)
We examined whether the presence of higher education facilities made regional towns more attractive as potential residences. Metropolitan undergraduate students reported that they were more willing to live in a regional town with (vs. without) a university. Importantly, this applied regardless of whether they intended to work or study at the university. Perceived quality of life - defined as a combination of resident sociability and happiness, and the estimated amount of activities within the town - mediated the effect of university presence on residency likelihood ratings, suggesting that the presence of a university prompted participants to infer a higher quality of life for town residents. These results have implications for policy to counteract out-migration from regional areas, which threatens food security.